Respond to this Question
Similar Questions

math
Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8
asked by Anonymous on October 25, 2018 
s.s
do u know any good websites for kids that have a step by step instructions on how to make something...in greek art...that sounds realy confusing srry but try to understand
asked by britt on January 5, 2008 
Art
I have looked almost everywhere on the inernet but i cant find any art websites that will show me stepbystep how to draw a school cafeteria do you all kno any websites that i can go to
asked by DeeDee on October 15, 2008 
ALGEBRA HELP
When solving the equation, what property was used to go from step 3 to step 4? Step 1: (2x+3= x18 Step 2: 2x3=x18 Step 3: 3=3x18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE
asked by cv on October 21, 2013 
Math
William multiplied (2x+13y)(0.5x) and got the wrong solution. Review his work and identify the step in which William made his first error. Step 1 (2x+13y)(0.5x) Step 2 (0.5x)(2x3y+1) Step 3 0.5x(2x)0.5x(3y)0.5x(1)
asked by Cherie on June 10, 2019 
Geometry
A parabola has a focus of F(2,8.5) and a directrix of y=9.5. The point P(x,y) represents any point on the parabola, while D(x,9.5) represents any point on the directrix. Maria was asked to use the distance formula to write an
asked by lilbaby on December 4, 2018 
Chemistry
In a chain mechanism, a reaction in which two free radicals combine to form a stable molecule would be called the A) initiation step B) termination step C) propagation step D) inhibition step E) branching step
asked by Haley on April 7, 2015 
Algebra help
f(x)=x^34x^2x+4 How do I find the xintercept for this? This is from my book: step 1: 0=x^34x^2x+4 step 2: 0=x^2(x4)+(1)(x4) step 3: 0=(x^21)(x4) I know how to solve once I get to step 3, but in step 2, I don't know what
asked by Claure on June 16, 2009 
math
An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,
asked by oscar on September 4, 2015 
math
An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,
asked by oscar on September 4, 2015